Various representations of Bulgarian Characters in Turkish films and television series: A sociological analysis - ÇOBAN, MELİH (My University, 2021)
Cinematic works like movies and television series include various social representations. These representations may emanate from political, cultural, social, economic and historical sources. A type of social representation common in cinematic products is the portrayal of members of different ethnic and/or national groups through various character typologies. One of the national groups represented in Turkish cinema is Bulgarians whom Turks have encountered for centuries. In this respect, this study aims to analyse various representations of Bulgarians in Turkish movies and television series in the light of various historical, political and social factors. To this aim, ten films and five television series produced between 1954 and 2019 have been studied. The study is based on two main research problematics: in which periods and under what conditions these cinematic works were produced and through which character categories Bulgarians were portrayed. It has been observed that these cinematic works have been produced, following the initiation of mistreatments by the Bulgarian state of her Turkish minority, with this theme and other themes like the Macedonian issue and that while characters representing the Bulgarian state have mostly been portrayed as villains, civilian Bulgarians have mostly been described as friendly characters. Same themes and characters have been adapted in the period of normalisation between two countries in a traditionalised way.

Filmler ve televizyon dizileri gibi sinematik ürünler pek çok toplumsal temsili içlerinde barındırır. Bu temsiller, siyasi, sosyal, kültürel, ekonomik ve tarihi kaynaklardan beslenebilmektedir. Sinematik ürünlerde sıkça rastlanılan bir toplumsal temsil türü, farklı etnik ve/veya ulusal topluluklara mensup bireylerin çeşitli karakter tiplemeleri üzerinden betimlenmesidir. Türk sinemasında temsillerine rastlanan ulusal topluluklardan birisi de Türklerin yüzyıllardır ilişki içinde olduğu Bulgarlardır. Bu bağlamda bu araştırmanın amacı, Türk sineması ve televizyon dizilerinde Bulgarların farklı temsillerini çeşitli tarihi, siyasi ve sosyal faktörlerin ışığında incelemektir. Bu açıdan, 1954 ve 2019 seneleri arasında çekilmiş on film ve beş televizyon dizisi incelenmiştir. Çalışma, Türk sinemasında Bulgar karakterler içeren sinematik ürünlerin hangi dönemlerde ve hangi koşullar ışığında çekildiği ve Bulgarların hangi karakter kategorileri üzerinden temsil edildiği şeklinde iki temel araştırma sorusuna dayanmaktadır. Bulgaristan’daki Türk azınlığına yönelik kötü muamelelerin başlamasını takiben söz konusu sinematik çalışmaların bu tema ve Makedonya sorunu gibi bir tarihi tema çerçevesinde yapıldığı ve Bulgaristan devletini temsil eden karakterlerin genelde düşman, Bulgar sivillerin ise iyi karakterler olarak gösterildiği gözlenmiştir. Aynı temaların ve karakter temsillerinin kullanımı, iki ülke arası ilişkilerin normalleştiği yıllarda da geleneksel bir şekilde devam etmiştir.
Türk film ve televizyon dizilerinde Bulgar karakterlerin farklı temsilleri: Sosyolojik bir analiz
Keywords: Türk Sineması; Bulgarlar; Temsil; Film; Televizyon Dizileri; Turkish Cinema; Bulgarians; Representation; Television Series